How restudy decisions affect overall comprehension for seventh‐grade students. (12th June 2017) - Thiede, Keith W.; Redford, Joshua S.; Wiley, Jennifer; Griffin, Thomas D.
Abstract : Background: Self‐regulated learning requires accurate monitoring and effective regulation of study. Little is known about how effectively younger readers regulate their study. Aims: We examined how decisions about which text to restudy affect overall comprehension for seventh‐grade students. In addition to a Participant's Choice condition where students were allowed to pick texts for restudy on their own, we compared learning gains in two other conditions in which texts were selected for them. The Test‐Based Restudy condition determined text selection using initial test performance – presenting the text with the lowest initial test performance for restudy, thereby circumventing potential problems associated with inaccurate monitoring and ineffective regulation. The Judgement‐Based Restudy condition determined text selection using metacognitive judgements of comprehension – presenting the text with the lowest judgement of comprehension, thereby circumventing potential problems associated with ineffective regulation. Sample: Four hundred and eighty seventh‐grade students participated. Method: Students were randomly assigned to conditions in an experimental design. Results and conclusions: Gains in comprehension following restudy were larger for the Test‐Based Restudy condition than for the Judgement‐Based Restudy condition or the Participant's Choice condition. No differences in comprehension were seen between the Judgement‐Based Restudy and Participant's Choice conditions. These results suggest seventh graders can systematically use their monitoring to make decisions about what to restudy. However, the results highlight how inaccurate monitoring is one reason why younger students fail to benefit from self‐regulated study opportunities.